The standby book : Activities for the language classroom. - Lindstromberg, Seth. (New York : Cambridge university press, 2000)
A rich resource for teachers of general English courses, groups of business and professional people and students of English for academic purposes.
Includes bibliography and index.
Keywords: Languages, Modern -- Study and teaching; Fremdsprachenunterricht; Lehrmittel